Empowerment of the Community Through KKN: Raising Awareness of Nutrition and the Risks of Waste for a Sustainable Sedulang Village: Pemberdayaan Masyarakat Melalui KKN: Edukasi Bahaya Sampah dan Kesadaran Gizi Menuju Desa Sedulang Berkelanjutan - Hanggara Arifian; Habibah Nur Rahmawati; Nashwa Azwariyana; Bayu Sandi Fajar; Andi Rangga Purwanto; Rachel Maria Tinambungan; Indra Angelina Seru; Sabilla Fajar Arnetta; Hieskya Anatasya Upa; Haikal Izhar Annazhari; Widodo (Jurnal Abdita Naturafarm, 2026)
Students have a duty to assist the community in addition to their roles as scholars.  Community Service Programs (KKN) provide a transformative framework for putting knowledge into practice.  Environmental cleanliness and nutritional knowledge were among the village issues that the KKN program addressed in Sedulang Village, Muara Kaman District, Kutai Kartanegara Regency.  Outreach on stunting and Dengue Fever (DHF) was part of the work program, as in creating eco-friendly briquettes and environmental education via the "See Trash, Take It" (LISA) campaign.  The community's awareness between illness transmission and unclean surroundings has grown as a result of the DHF outreach. The stunting outreach, meanwhile, helped moms and young women understand how crucial nutrition is to a child's growth and development.  By encouraging active community participation in village cleanliness and providing training on creating briquettes from organic waste as an alternative energy source, the LISA movement brought tangible results.  This program links local issues like waste, flooding, and the state of stilt houses with global solutions for health, clean energy, and sustainable village development. It does this by taking an approach that is in line with Sustainable Development Goals (SDGs) points 12 (responsible consumption and production) and 3 (healthy and prosperous lives).